Insights into the protein domains of C-VI TRIM subfamily in viral infection - Patrick, Bbumba; Lo, Yan-Chung; Su, Wen-Chi (Frontiers in Cellular and Infection Microbiology, 2025)
Tripartite motif (TRIM) proteins, defined by their conserved RBCC domain architecture, play key roles in various cellular processes and virus-host interactions. In this review, we focus on Class VI TRIM proteins, including TRIM24, TRIM28, and TRIM33, highlighting the distinct functional attributes of their RING, B-BOX1, B-BOX2, COILED COIL, PHD, and BRD domains in viral infection. Through multiple sequence alignment, we delineate both the conserved and divergent features within this subclass, underscoring the uniqueness of Class VI TRIM protein. Additionally, we explore the post-translational modifications (PTMs) of Class VI TRIM proteins including their functional differences in modulating viral infection. Moreover, we examine the C-VI TRIM protein complexes and their significant contributions to the antiviral response. Furthermore, we discuss small molecule ligands targeting Class VI TRIM domains, with a focus on druggable structural motifs. Understanding the multi-domain features of TRIM proteins is crucial for developing effective antiviral strategies and the therapeutic modulation of their activity.